2014
DOI: 10.1371/journal.pone.0108861
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Tegument Protein pp65 Is Detected in All Intra- and Extra-Axial Brain Tumours Independent of the Tumour Type or Grade

Abstract: Human cytomegalovirus (HCMV) has been indicated being a significant oncomodulator. Recent reports have suggested that an antiviral treatment alters the outcome of a glioblastoma. We analysed the performance of commercial HCMV-antibodies applying the immunohistochemical (IHC) methods on brain sample obtained from a subject with a verified HCMV infection, on samples obtained from 14 control subjects, and on a tissue microarray block containing cores of various brain tumours. Based on these trials, we selected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 58 publications
(89 reference statements)
4
60
0
Order By: Relevance
“…With current standard therapy, median overall survival (OS) for GBM patients is less than 15 mo after diagnosis. 1,2 An active HCMV infection, as determined by HCMV protein expression, can be detected in tumor cells in 90-100% of GBM patients; [3][4][5][6][7][8] however, the infection is absent in healthy surrounding tissues, indicating a potential oncomodulatory or oncogenic role of HCMV. We found that the median OS of GBM patients correlates with the grade of HCMV infection in tumor tissue.…”
mentioning
confidence: 99%
“…With current standard therapy, median overall survival (OS) for GBM patients is less than 15 mo after diagnosis. 1,2 An active HCMV infection, as determined by HCMV protein expression, can be detected in tumor cells in 90-100% of GBM patients; [3][4][5][6][7][8] however, the infection is absent in healthy surrounding tissues, indicating a potential oncomodulatory or oncogenic role of HCMV. We found that the median OS of GBM patients correlates with the grade of HCMV infection in tumor tissue.…”
mentioning
confidence: 99%
“…Higher CMV levels have also been suggested to be correlated with poorer patient survival [6]. Human CMV pp65 was reported to be detected by another group in all brain tumors independent of type of grade [7]. CMV in tumors has also been detected in other tumor types in recent years, including breast cancer and metastases [26], medulloblastoma [27] and rhabdomyosarcoma [25].…”
Section: Consensus and Controversymentioning
confidence: 98%
“…Since the initial study by Cobbs et al [3] reporting the identification of CMV antigens and nucleic acids in glioblastoma patients, there have been numerous additional independent studies, which have confirmed and built on these findings [e.g., [4][5][6][7][8][9]. One study performed optimization of immunohistochemical techniques and was able to detect CMV IE1 in 100 % of glioblastomas and 82 % of low grade glioma [5].…”
Section: Consensus and Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies utilizing IHC have found pp65 positivity in gliomas, medulloblastomas, CNS lymphoma and meningiomas. 21 Others have found that 25% of patients with GBM had detectable levels of a CMV micro RNA (miR-UL112-3p) in their blood. 22 (Table 1)…”
Section: Detection In Gliomasmentioning
confidence: 99%